KOMUNIKASI CEPAT TANGGAP PENANGANAN DAN PENCEGAHAN RABIES MELALUI ANAK-ANAK SEKOLAH DASAR DI KOTA KUPANG, NUSA TENGGARA TIMUR - Larry Richard Wellem Toha; Nancy Diana Frederika Katarina Foeh; Yohanes Timbun Raja Mangihut Ronael Simarmata; Meity Marviana Laut; Muhajirin Dean; Maria Laurenci Fanny Permata Kale (Jurnal Media Tropika, 2026)
Rabies is a fatal zoonotic disease that remains a public health problem in East Nusa Tenggara Province, including Kupang City. Elementary school-aged children are a vulnerable group to bites from Rabies-Transmitting Animals (HPR) due to limited knowledge and risky behavior when interacting with animals. This community service activity aims to increase students' understanding and awareness of the dangers of rabies, its transmission, prevention, and first-aid steps after a bite through a learning-by-play approach. The activity was carried out in October 2025 at SDN Nunbaun Sabu, Kupang City, involving approximately 100 students. The methods used included interactive counseling, educational video screenings, educational games, and a 15-minute simulation of emergency wound washing using soap and running water. Evaluation was carried out through participatory observation and structured question-and-answer sessions. The results of the activity showed an increase in students' understanding of the dangers of rabies and basic preventive measures. The game-based educational approach has proven effective in conveying health messages and has the potential to shape children into rabies education agents within the family and community.